Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.7 - Simplifying Complex Fractions - Exercise Set: 39

Answer

$\dfrac{\dfrac{6}{x-5}+\dfrac{x}{x-2}}{\dfrac{3}{x-6}-\dfrac{2}{x-5}}=\dfrac{(x+4)(x-6)}{x-2}$

Work Step by Step

$\dfrac{\dfrac{6}{x-5}+\dfrac{x}{x-2}}{\dfrac{3}{x-6}-\dfrac{2}{x-5}}$ Evaluate the sum indicated in the numerator and the substraction indicated in the denominator: $\dfrac{\dfrac{6}{x-5}+\dfrac{x}{x-2}}{\dfrac{3}{x-6}-\dfrac{2}{x-5}}=\dfrac{\dfrac{6(x-2)+x(x-5)}{(x-5)(x-2)}}{\dfrac{3(x-5)-2(x-6)}{(x-6)(x-5)}}=...$ $...=\dfrac{\dfrac{6x-12+x^{2}-5x}{(x-5)(x-2)}}{\dfrac{3x-15-2x+12}{(x-6)(x-5)}}=\dfrac{\dfrac{x^{2}+x-12}{(x-5)(x-2)}}{\dfrac{x-3}{(x-6)(x-5)}}=...$ Evaluate the division: $...=\dfrac{x^{2}+x-12}{(x-5)(x-2)}\div\dfrac{x-3}{(x-6)(x-5)}=...$ $...=\dfrac{(x^{2}+x-12)(x-6)(x-5)}{(x-5)(x-2)(x-3)}=...$ Factor the first parentheses in the numerator and simplify: $...=\dfrac{(x+4)(x-3)(x-6)(x-5)}{(x-5)(x-2)(x-3)}=...$ $...=\dfrac{(x+4)(x-6)}{x-2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.